Hygroscopic properties of solid agro-industrial by-products used in solid-state fermentation - Casciatori, Fernanda Perpetua [UNESP]; Laurentino, Carmem Lucia [UNESP]; Zanelato, Alex Izuka [UNESP]; Thomeo, Joao Claudio [UNESP] (Elsevier B.V., 2015)
One of the main drawbacks in operating solid-state fermentation (SSF) bioreactors is the reduction in moisture content (MC) of the solid phase due to microbiological and physicochemical issues. Therefore, heat and mass transfer models require hygroscopic information concerning the solid substrate. This contribution addresses the study of the sorption isotherms of sugarcane bagasse (SCB) and wheat bran (WB) obtained using the static gravimetric method, with temperature and water activity as the controlled variables. The Oswin model was selected to construct the sorption isotherm for SCB, and the Halsey model, modified in the present study, for WB. The Bates and Watts curvature measurements and the Box parameter bias were used to analyze the nonlinear behavior and assess the goodness of the fitting process. Fermentative assays were carried out in glass flasks for the production of endoglucanase employing the fungus Myceliophthora thermophila I-1D3b, controlling the environmental water activity, in order to assess the influence of the loss of moisture from the solid phase on fungal metabolic activity. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Sorption isotherms; Moisture content; Enzymes; Solid-state fermentation; Agro-industrial by-products